Pengaruh Pembelajaran Berbasis Proyek Berbantuan Media Berbasis Lectoran Inspire terhadap Keterampilan Proses Sains Siswa - Surayya, Rania; Anwar, Yunita Arian Sani; Loka, I Nyoman (FKIP University of Mataram, 2024)
This research aims to determine the effect of the Project Based Learning (PjBL) model assisted by lectora inspire media on the chemistry science process skills of 10th grade students at SMAN 1 Lembar. This research uses a quasi eksperimental method. The research population consists of all 10th grade students at SMAN 1 Lembar, totaling 134 students from 4 classes. The sample was selected using cluster random sampling techniques. The research samples are Class X MIPA 1 as the experimental class using the Project Based Learning (PjBL) model assisted by lectora inspire based media and Class X MIPA 2 as the control class using conventional learning methods. Data collected include the results of science process skills tests and observations of teacher activities using the Project Based Learning (PjBL) model. The results of the science process skills test show that the N-Gain score for the experimental class is greater than the N-Gain score for the control class. The Presentation of the effectiveness of the PjBL model on students is as follows: 70.97% of students are not effective, 19.35% are less effective, 6.45% are moderately effective, dan 3.23% are effective. The t-test results indicate that the t-value > t-table. Observation of teacher activities using the Project Based Learning (PjBL) model has improved from the ‘good’ category to ‘very good’.